2016
DOI: 10.3390/rs8030177
|View full text |Cite
|
Sign up to set email alerts
|

Global and Regional Variability and Change in Terrestrial Ecosystems Net Primary Production and NDVI: A Model-Data Comparison

Abstract: Abstract:The net primary productivity (NPP) is commonly used for understanding the dynamics of terrestrial ecosystems and their role in carbon cycle. We used a combination of the most recent NDVI and model-based NPP estimates (from five models of the TRENDY project) for the period 1982-2012, to study the role of terrestrial ecosystems in carbon cycle under the prevailing climate conditions. We found that 80% and 67% of the global land area showed positive NPP and NDVI values, respectively, for this period. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 52 publications
2
39
0
3
Order By: Relevance
“…Rafique et al . () also found a consistent decreasing trend for vegetation coverage in the northeastern part of China. In addition, northern China has been subjected to extensive ecological restoration projects (such as “the Three North Forest Shelterbelt Program”).…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Rafique et al . () also found a consistent decreasing trend for vegetation coverage in the northeastern part of China. In addition, northern China has been subjected to extensive ecological restoration projects (such as “the Three North Forest Shelterbelt Program”).…”
Section: Introductionsupporting
confidence: 55%
“…The reduction in precipitation, particularly after 2000s, seems to have caused a reversal of the greening trend of growing season observed before the 2000s (Peng et al, 2011). Rafique et al (2016) also found a consistent decreasing trend for vegetation coverage in the northeastern part of China. In addition, northern China has been subjected to extensive ecological restoration projects (such as "the Three North Forest Shelterbelt Program").…”
Section: Introductionmentioning
confidence: 54%
“…Lett. 12 (2017) 084015 larger than in other model estimates, which range between 53-72 Pg C (Rafique et al 2016). A comparison of the simulated NPP for the different PFTs reveals that JSBACH generally tends to be overproductive especially for forests ( figure S3).…”
Section: Factor Separation Approachmentioning
confidence: 83%
“…Many studies have been conducted on evaluation and intercomparison of carbon cycle components of land models (Johns et al, 2011;Taylor et al, 2011;Zaehle et al, 2014;Rafique et al, 2016b), and most of these studies show large discrepancies in modeled carbon stocks and fluxes. For example, the Coupled Model Intercomparison Project (C4MIP) reported that carbon uptake responses to a doubling of atmospheric CO 2 concentrations varied from 100 to 800 Gt carbon amongst 11 models for the period 1850-2100 years (Friedlingstein et al, 2006;Arora et al, 2011).…”
Section: Introductionmentioning
confidence: 99%